SPECIAL NEEDS SCHOOL B & C WITH TROPICAL ARCHITECTURE APPROACH IN MEDAN CITY - Panjaitan, Rachel Anugerah Laurelia; Aulia , Dwira Nirfalini (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Education has an important role in the life of every human being, including children with special needs (disability) who have limitations in carrying out their daily activities. Based on data from the 2020 National Economic Survey (SUSENAS), it shows that only 29.61 percent of children with disabilities have graduated from elementary school, and almost 2 out of 10 children with disabilities have never received education. One of the causes of many children with disabilities never attending school is because of the lack of learning facilities such as special needs schools. A special needs school is an educational institution intended for children with certain special needs, which is used as a forum for learning activities and talent interest training. The design of the B & C special needs school with a Tropical Architectural Approach concentrates on creating comfort and safety in the space and building environment, both natural and artificial, by utilizing the potential of the local climate. A tropical architectural approach is applied as a solution to combine buildings, users and climatic conditions around the site.